The effect of corrective exercises accompanied by mechanical feedback on some kinematic indicators and learning how to perform volleyball spiking for students - Khader Abbas , Ithraa Abdul; Mushref , Ameer Jaber; Ameen Shalash , Maher Jaafar (مجلة دراسات وبحوث التربية الرياضية, 2024)
The aim of the research was to: Identify some kinematic indicators affecting learning to perform crushing multiplication for students at the College of Physical Education and Sports Sciences/University of Kufa. The researchers used the experimental approach with two equal groups, and the research sample was intentionally chosen, represented by students from the college of physical education. and Sports Sciences/University of Kufa, which numbered (24) students for the academic year 2023-2024. The statistical analysis program (SPSS) was used to obtain the results. The researchers concluded that the corrective exercises accompanied by mechanical feedback showed a positive effect on some kinematic indicators and learning the skill of hitting the volleyball. For students, the researchers recommended the necessity of applying exercises that target mechanical indicators because of their effective role and basis in learning technical performance